A clinical audit on specimen collection procedures: unveiling soft skill components in structured nursing clinical assessments - Nurumal, Mohd. Said; Jamaludin, Thandar Soe @ Sumaiyah; Ahmad, Norfadzilah; Muhammad, Siti Aeshah @ Naznin; Mei Chan, Chong (Universiti Putra Malaysia, 2025)
Introduction: Specimen collection procedures are commonly employed in clinical settings, requiring nurses to engage with diverse patients. Proficiency in these procedures demands not only technical skills (hard skills) but also adeptness in soft skills for effective patient care. However, current structured clinical skill assessments on specimen collection procedures predominantly emphasize technical skills, often overlooking the assessment of crucial soft skills. This study aims to examine the components of soft skill elements in objectively structured clinical skill assessments of specimen collection procedures in the undergraduate nursing programme. Materials and method: A clinical audit was conducted on five sets of retrospective structured clinical skill assessment exam questions, utilizing the Clinical Skill Assessment Index VII (CSAI-VII) instrument. Result: The identified specimen collection procedures included urine specimen collection for culture and sensitivity tests (60%), sputum specimen collection for culture and sensitivity tests (20%), and other procedures like Vulva swabbing tests (20%). However, certain specimen collection procedures, such as blood and stool specimen collection, were not found in the collected OSCE documents. Regarding soft skill elements, communication skills were universally present (100%), while other vital soft skills were notably absent from the specimen collection procedure’s checklist/rubric. Conclusion: This study reveals areas for improvement in structured clinical skill assessments for specimen collection procedures. Emphasizing the necessity for well-structured clinical skill assessment exam questions, this research underscores the importance of cultivating graduate nurses proficient in both technical and soft skills to meet the demands of the contemporary healthcare system.